Zinc(II) {2}-Metallacoronates and {2}-Metallacryptates based on Dipicolinoylbis( N,N-diethylthiourea): Structures and Biological Activities - Canh Dinh Le; Chien Thang Pham; Hung Huy Nguyen (My University, 2019)
Zinc(II) {2}-Metallacoronates and {2}-Metallacryptates based on Dipicolinoylbis( N,N-diethylthiourea): Structures and Biological Activities
Keywords: Zinc(II)